Consensus recommendations for the treatment and management of patients with Fabry disease on migalastat: a modified Delphi study - Bichet, Daniel G.; Hopkin, Robert J.; Aguiar, Patrício; Allam, Sridhar R.; Chien, Yin-Hsiu; Giugliani, Roberto; Kallish, Staci; Kineen, Sabina; Lidove, Olivier; Niu, Dau-Ming; Olivotto, Iacopo; Politei, Juan; et al. (Frontiers in Medicine, 2023)
Objective Fabry disease is a progressive disorder caused by deficiency of the α-galactosidase A enzyme (α-Gal A), leading to multisystemic organ damage with heterogenous clinical presentation. The addition of the oral chaperone therapy migalastat to the available treatment options for Fabry disease is not yet universally reflected in all treatment guidelines. These consensus recommendations are intended to provide guidance for the treatment and monitoring of patients with Fabry disease receiving migalastat. Methods A modified Delphi process was conducted to determine consensus on treatment decisions and monitoring of patients with Fabry disease receiving migalastat. The multidisciplinary panel comprised 14 expert physicians across nine specialties and two patients with Fabry disease. Two rounds of Delphi surveys were completed and recommendations on the use of biomarkers, multidisciplinary monitoring, and treatment decisions were generated based on statements that reached consensus. Results The expert panel reached consensus agreement on 49 of 54 statements, including 16 that reached consensus in round 1. Statements that reached consensus agreement are summarized in recommendations for migalastat treatment and monitoring, including baseline and follow-up assessments and frequency. All patients with Fabry disease and an amenable mutation may initiate migalastat treatment if they have evidence of Fabry-related symptoms and/or organ involvement. Treatment decisions should include holistic assessment of the patient, considering clinical symptoms and organ involvement as well as patient-reported outcomes and patient preference. The reliability of α-Gal A and globotriaosylsphingosine as pharmacodynamic response biomarkers remains unclear. Conclusion These recommendations build on previously published guidelines to highlight the importance of holistic, multidisciplinary monitoring for patients with Fabry disease receiving migalastat, in addition to shared decision-making regarding treatments and monitoring throughout the patient journey. GRAPHICAL ABSTRACT